Effects of filling ratio and condenser temperature on the thermal performance of a neon cryogenic oscillating heat pipe. (January 2018) - Liang, Qing; Li, Yi; Wang, Qiuliang
Highlights: A copper cryogenic OHP with neon as the working fluid is manufactured. Effects of filling ratio and condenser temperature on the thermal performance are discussed. A correlation based on the available experimental data sets is established. Abstract: A cryogenic oscillating heat pipe (OHP) made of a bended copper capillary tube is manufactured. The lengths of the condenser section, adiabatic section and evaporator section are 100, 280 and 100 mm, respectively. Neon is used as the working fluid. Effects of liquid filling ratio and condenser temperature on the thermal performance of the OHP are studied. A correlation based on the available experimental data sets is proposed to predict the thermal performance of the neon cryogenic OHP with different filling ratios and condenser temperature. Compared with the experimental data, the average standard deviation of the correlation is about 15.0%, and approximately 92.4% of deviations are within ±30%.